Terminologia al servizio della traduzione - Kardos, Orsolya (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(–scale-factor)*111.50px); top: calc(var(–scale-factor)*199.36px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.932415);" role="presentation">While the theory of terminology was originally developed to harmonise concepts in <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*213.16px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.948741);" role="presentation">technical field<span dir="ltr" style="left: calc(var(–scale-factor)*139.82px); top: calc(var(–scale-factor)*213.16px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.919874);" role="presentation">s, with the emergence of translation studies, it became <span dir="ltr" style="left: calc(var(–scale-factor)*409.99px); top: calc(var(–scale-factor)*213.16px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.871511);" role="presentation">soon <span dir="ltr" style="left: calc(var(–scale-factor)*436.51px); top: calc(var(–scale-factor)*213.16px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.922593);" role="presentation">clear that some of <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*226.96px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927477);" role="presentation">the pre-<span dir="ltr" style="left: calc(var(–scale-factor)*109.46px); top: calc(var(–scale-factor)*226.96px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.942353);" role="presentation">conditions of terminological standardisation, such as the absence of synonymy and <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*240.79px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.986163);" role="presentation">polysemy, are not fulfilled in <span dir="ltr" style="left: calc(var(–scale-factor)*220.49px); top: calc(var(–scale-factor)*240.79px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.939097);" role="presentation">professional communication. An<span dir="ltr" style="left: calc(var(–scale-factor)*380.23px); top: calc(var(–scale-factor)*240.79px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.957445);" role="presentation">other issue is the lack of <span dir="ltr" style="left: calc(var(–scale-factor)*507.94px); top: calc(var(–scale-factor)*240.79px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.08657);" role="presentation">full <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*254.59px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.894868);" role="presentation">equivalence in some cases or the diachronic variation of terms. New approaches to terminology <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*268.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.926281);" role="presentation">take these phenomena into account, therefore they are better suited <span dir="ltr" style="left: calc(var(–scale-factor)*409.75px); top: calc(var(–scale-factor)*268.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.995553);" role="presentation">to form<span dir="ltr" style="left: calc(var(–scale-factor)*446.98px); top: calc(var(–scale-factor)*268.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.957901);" role="presentation">ing <span dir="ltr" style="left: calc(var(–scale-factor)*466.90px); top: calc(var(–scale-factor)*268.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915782);" role="presentation">the basi<span dir="ltr" style="left: calc(var(–scale-factor)*505.42px); top: calc(var(–scale-factor)*268.39px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.994516);" role="presentation">s of <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*282.19px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914255);" role="presentation">translation-<span dir="ltr" style="left: calc(var(–scale-factor)*125.42px); top: calc(var(–scale-factor)*282.19px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.974961);" role="presentation">oriented terminology. This article explores terminology <span dir="ltr" style="left: calc(var(–scale-factor)*410.47px); top: calc(var(–scale-factor)*282.19px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.845751);" role="presentation">issues <span dir="ltr" style="left: calc(var(–scale-factor)*444.82px); top: calc(var(–scale-factor)*282.19px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.95594);" role="presentation">that a translator <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.969589);" role="presentation">usually encounters when translating <span dir="ltr" style="left: calc(var(–scale-factor)*262.97px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914129);" role="presentation">technical <span dir="ltr" style="left: calc(var(–scale-factor)*313.75px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.968728);" role="presentation">texts and <span dir="ltr" style="left: calc(var(–scale-factor)*368.11px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.853217);" role="presentation">argues <span dir="ltr" style="left: calc(var(–scale-factor)*406.75px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">that <span dir="ltr" style="left: calc(var(–scale-factor)*432.06px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.96204);" role="presentation">a translator <span dir="ltr" style="left: calc(var(–scale-factor)*497.06px); top: calc(var(–scale-factor)*295.99px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.836475);" role="presentation">needs <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*309.79px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.892868);" role="presentation">terminological competence in order to be able to address these challenges.